ANALISIS PERBANDINGAN KEKERASAN PERMUKAAN POROS AXLE SHAFT JENIS MATERIAL S-43 YANG DILAKUKAN DENGAN PROSES INDUKSI HARDENING PADA MESIN 12-9 B “KORA NETUREN” - Sumiyanto, Sumiyanto (Bina Teknika, 2018)
Hardening process is the process of hardening in a material heated above the critical temperature and then cooled quickly (quenched) to reach room temperature in order to improve hardness and strength of a material. Hardening process carried out on all the tools and some equipment or machine parts that have a major benefit is to obtain a higher hardness.This research was conducted on 447 SNCM alloy steel which is a medium carbon steel grade that is equal to 0:30 to 0:38%. This type of steel can be hardened by heat treatment process that is by heating the steel at a temperature of 500oC, for 1 hour as the preheating temperature (preheated). Then proceed to the process of hardening, namely austenising temperature with 900oC with holding time 2 hours and cooled with oil and then water in tempering with holding time 1 hour at 300oC, 400oC and 500oC.From research result obtained using the Vickers hardness values that increase occurred in materials that undergo a process of hardening at 900oC cooling using water media, whereas the lowest hardness value occurs in the original material.